Acne vulgaris and self-confidence among medical students of universitas jenderal achmad yani class of 2023 - Dinda F M Afifah; Arlisa Wulandari; Rina Munirah (ACTA Medical Health Sciences, 2025)
Acne vulgaris is a common inflammatory disorder that can affect psychological well-being in adolescents and young adults. This study aimed to examine the association between clinically confirmed acne vulgaris and self-confidence among undergraduate medical students. An analytical cross-sectional design was applied, involving 112 students from the Faculty of Medicine, Universitas Jenderal Achmad Yani, Class of 2023, recruited through consecutive sampling. Acne vulgaris was diagnosed clinically by a board-certified dermatologist, whereas self-confidence was assessed using the Ratnasari (2021) self-confidence questionnaire and the Rosenberg Self-Esteem Scale. Chi-square analysis was used to evaluate associations between acne status and self-confidence levels, with significance set at p < 0.05. Ethical approval was obtained from the Faculty of Medicine Ethics Committee (Approval No. 031/UM1.08/2024). Of the 112 respondents, 62 students (55.4%) were diagnosed with acne vulgaris. Most participants demonstrated high self-confidence based on both the Ratnasari questionnaire (67 students, 59.8%) and the Rosenberg scale (68 students, 60.7%). Statistical analysis showed no significant relationship between the presence of acne vulgaris and self-confidence (Ratnasari: p = 0.673; Rosenberg: p = 0.304). In conclusion, although acne vulgaris was common in this population, it was not associated with self-confidence levels. Further studies are recommended to explore additional psychological or environmental factors that may influence self-confidence among medical students.   DOI : 10.35990/amhs.v4n2.p61-67   REFERENCES Tan ST, Firmansyah Y, Elizabeth J. Enhancing adolescent self-confidence by controlling acne. Jurnal Pengabdian Mandiri. 2022;1(5):723–730. Sibero HT, Anggraini DI. Prevalence and epidemiological profile of acne vulgaris in Lampung Province. Jurnal Kedokteran Universitas Lampung. 2019;3(2):308–312. Teresa A. Adult acne vulgaris: Etiology, pathogenesis, and current management. Jurnal Kedokteran Universitas Palangka Raya. 2020;8(1):952–964. Saiya GD, Manuputty AG, Saiya AF, Yakobus S, Titaley CR, Tanamal RS. Relationship between acne vulgaris severity and self-confidence among medical students at Universitas Pattimura Ambon. PAMERI: Pattimura Medical Review. 2023;5(1):47–54. Sitohang MN, Teresa A. Literature review: Relationship between facial hygiene behavior and acne vulgaris. Jurnal Kedokteran Universitas Palangka Raya. 2022;10(1):13–17. Murlistyarini S. Acne Vulgaris. Malang: Universitas Brawijaya Press; 2019. Annisa F, Sulistiasari R. Relationship between sleep quality and acne vulgaris incidence in patients at Dr. Nur Afni Practice, Medan, 2020. Jurnal Kedokteran Ibnu Nafis. 2021;10(1):49–52. Sachio A, Toruan VML, Yuniati Y. Relationship between acne vulgaris severity and quality of life using the Dermatology Life Quality Index (DLQI). Jurnal Kebidanan Mutiara Mahakam. 2020;8(2):77–83. Rais MR. Self-confidence and its development in adolescents. Al-Irsyad: Jurnal Pendidikan dan Konseling. 2022;12(1):40–47. Fitri E, Zola N, Ifdil I. Profile of adolescent self-confidence and influencing factors. JPPI (Jurnal Penelitian Pendidikan Indonesia). 2018;4(1):1–5. Xu S, Zhu Y, Hu H, et al. The analysis of acne increasing suicide risk. Medicine. 2021;100(24):e26035. Tayel K, Attia M, Agamia N, Fadl N. Acne vulgaris: Prevalence, severity, and impact on quality of life and self-esteem among Egyptian adolescents. Journal of the Egyptian Public Health Association. 2020;95:1–7. Ompi EE, David L, Opod H. Relationship between self-confidence and acne vulgaris in adolescents at SMAN 7 Manado. eBiomedik. 2016;4(1). Aryani DT, Riyaningrum W. Relationship between acne vulgaris and self-confidence in students at Universitas Muhammadiyah Purwokerto, class of 2021. Jurnal Kesehatan Tambusai. 2022;3(3):434–441. Sitohang IBS, Wasitatmadja SM. Ilmu Penyakit Kulit dan Kelamin. Jakarta: Badan Penerbit Fakultas Kedokteran Universitas Indonesia; 2015. p. 288–289. Hasanah RL, Rianto Y, Riana D. Identification of acne vulgaris type in facial acne images using GLCM feature extraction and Extreme Learning Machine algorithm. Rekayasa. 2022;15(2):204–214. Wibisono EA, Indramaya DM, Rochmanti M. Retrospective study: Initial pharmacotherapy profile of new acne vulgaris patients. Jurnal Berkala Epidemiologi. 2020;8(3):236–245. Deliana R, Amalia R, Jusuf NK. Relationship between body mass index and acne vulgaris in students at SMA Negeri 7 Medan. Cermin Dunia Kedokteran. 2019;46(4):253–255. Fadilah AA. Correlation between psychological stress and the incidence of acne vulgaris. Jurnal Ilmiah Kesehatan Sandi Husada. 2021;10(2):390–395. Saragih DF, Opod H, Pali C. Relationship between self-confidence and acne vulgaris in senior high school students at SMA Negeri 1 Manado. eBiomedik. 2016;4(1). Harahap M. Anatomy and function of the skin. In: Harahap M, editor. Ilmu Penyakit Kulit. Jakarta: Hipokrates; 2000. p. 35–45. Ulfah N. Relationship between cosmetic exposure and acne vulgaris incidence in female medical students. Jurnal Health Sains. 2020;1(6):393–400. Ramadhianti S. Relationship between acne vulgaris incidence and self-confidence of female medical students at Universitas Islam Sumatera Utara. 2023. Kang S, Amagai M, Bruckner AL, Enk AH, Margolis DJ, McMichael AJ, et al. Acne vulgaris. In: Kang S, et al., editors. Fitzpatrick’s Dermatology. 9th ed. New York: McGraw-Hill Education; 2019. p. 1392–1412. Tanojo N, Anggraeni S. The use of dermoscopy to distinguish between pityrosporum folliculitis and acne vulgaris. 2023. Juliyanti J. Dermoscopy. Jurnal Pandu Husada. 2023;4(2):58–78. Mescher AL. Histology: Junqueira’s Text and Atlas. Jakarta: EGC; 2011. p. 364–373. Nabillah R. Prevalence of seborrheic dermatitis in dermatology outpatient clinic of RSUD Meuraxa Banda Aceh, 2016–2019. Jurnal Health Sains. 2021;2(1):112–119. Unzilla DA. Concept of self-confidence in adolescent girls. Educatio. 2016;2(2):43–52. Marbun KAF, Siagian IO, Sinaga H. Self-confidence and anxiety levels in final-year students completing their thesis at Institut Kesehatan Immanuel Bandung. Jurnal Kesehatan. 2023;12(2):321–332. Savira SI. Relationship between self-concept and self-confidence with social media usage intensity as a moderator in psychology students at Universitas Negeri Surabaya. E-Journal Unesa. 2021;8(2). Sulasih. Enhancing self-confidence through group guidance services. Hartamedia. 2016:1–71. Syam A, Amri A. The effect of self-confidence training based on IMM cadre system on student academic performance: A case study in the biology education program at Universitas Muhammadiyah Parepare. Jurnal Biotek. 2017;5(1):87–102. Lauster P. Tes Kepribadian. Diterjemahkan oleh D.H. Gulo. Jakarta: PT Gramedia Pustaka Utama; 1998. p. 1–13. Hulukati W, Djibran MR. Analysis of developmental tasks of students in the Faculty of Education, Universitas Negeri Gorontalo. Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik). 2018;2(1):73–80. Kamus Besar Bahasa Indonesia (KBBI). Kamus daring. Tersedia pada: https://kbbi.web.id/didik Matheus KG, Wungouw HPL, Rante SDT. Relationship between acne vulgaris incidence and self-confidence among female students at SMAN 3 Kupang. Cendana Medical Journal. 2018;6(3):369–375. Sugiyono. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta; 2019. p. 112–125. Maroqi N. Construct validity testing of the Rosenberg Self-Esteem Scale instrument using confirmatory factor analysis (CFA). Jurnal Pengukuran Psikologi dan Pendidikan Indonesia (JP3I). 2019;7(2):92–96. Ratnasari NIPD. Profil Kepercayaan Diri Remaja dengan Akne di SMA Dwijendra Denpasar. Bali: Institut Teknologi dan Kesehatan Bali; 2021. Suwarjana IK. Statistik Kesehatan. Yogyakarta: Penerbit Andi; 2016. p. 132.